Suid-Afrika benodig 'n Christelike alternatief op Marxisme en Neo-Marxisme - Plessis, P. G. W. du (Koers, 1985)
In this opening paper of the Conference commemorating 50 years of the existence of KOERS the chairman places KOERS in perspective. He looks back to two generations of work done by Calvinist scholars and comes to the conclusion that an era representing a certain trend of thought has been brought to a close. Up to now KOERS has been a prophet and has had a function to fulfil as such. For the future, he warns that we should not in utopian fervour expect everything beautiful of our Calvinist conceptions. KOERS has entered a new phase of existence and we cannot end the critical dialogue with Marxism and Neo-Marxism with the placid observation that Marxism is by definition atheistic and humanisitic and materialistic. In the present situation what is needed is not a hypocritical enlightenment versus an elitist post-enlightened attitude - we should rather strive to begin our renewals and self-criticism with a look at blessings and grace, which constitute the basis of life, and then employ humility, consideration, self-discipline, gratitude and love of the neighbour in creating a new lifestyle in which we can work toward peaceful co-existence in this country. Christian principles cannot be allowed to remain hanging in the sky but should be incarnated into daily attitudes and responses. A Christian alternative to wrong conditions means to make Marxism and Neo-Marxism redundant and barren in this country, and to fulfil our calling in God's world.